Nationalism and the issue of nation-building in the nineteenth century`s Georgian political thought - Dundua, Salome (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, we discuss two different directions about the Georgian nationalism of the 19th century: first we consider, thetrinity of language, homeland, faith - maybe one of the best classical formulations of nationalist project. And second, in the process of creation of the nation, in the course of research of the Georgian nation-building of that period, we can not avoid the role of printed media.
Keywords: nationalism; nation-building; education; language; Orthodoxy